PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN E-BOOK CERITA RAKYAT TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS V SDI LEMBANG BU’NE KECAMATAN TOMPOBULU KABUPATEN GOWA - Muanzir; Aliem Bahri; Sri Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Muanzir. 2026. The Effect of Utilizing E-book Folklore Learning Media on the Reading Comprehension Ability of Fifth Grade Students at SDI Lembang Bu’ne, Tompobulu District, Gowa Regency. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar. Supervisors: I. Aliem Bahri and II. Sri Rahayu.This study was motivated by the problem of low reading comprehension ability among fifth grade students, which was influenced by the limited use of creative and innovative learning media in the teaching and learning process. The purpose of this study was to analyze the effect of using folklore e-book learning media on the reading comprehension ability of fifth grade students at SDI Lembang Bu’ne.The method used in this research was an experimental method with a Pre-Experimental Design, specifically the One Group Pretest-Posttest Design. The research subjects consisted of 12 fifth grade students. Data were collected through a pretest and a posttest. The obtained data were then analyzed using descriptive and inferential statistics with the assistance of a t-test.The results of the study showed that the e-book learning media had a significant effect on the reading comprehension ability of fifth grade students at SDI Lembang Bu’ne, Tompobulu District, Gowa Regency. This can be seen from the improvement in students’ reading comprehension learning outcomes, as well as from the observation results indicating that the use of folklore e-book learning media had a positive impact on students’ learning activities, with a 100% increase in students’ reading comprehension results. The inferential data analysis showed that there was an effect of using e-book learning media, as evidenced by the results of the t-test calculation, where tcount = 51.00 and ttable = 2.201. Since tcount (51.00) > ttable (2.201), it can be concluded that the e-book learning media had a positive effect on the reading comprehension ability of fifth grade students at SDI Lembang Bu’ne, Tompobulu District, Gowa Regency.